2014
DOI: 10.1097/rct.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Pelvic Fluid in Males on Outpatient Magnetic Resonance Imaging Examinations

Abstract: Isolated fluid is greater than 7 times more common on outpatient pelvic MRIs in males younger than 30 years compared with men older than 49 years. Fluid rarely exceeded 10 mL or 6 cm(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Less than 10 mL fluid has been assumed normal in all age groups without evidence of underlying disease [2, 4, 22]. However in this study, 15% of females and 3% of males had more than 10 mL fluid during puberty transition.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Less than 10 mL fluid has been assumed normal in all age groups without evidence of underlying disease [2, 4, 22]. However in this study, 15% of females and 3% of males had more than 10 mL fluid during puberty transition.…”
Section: Discussionmentioning
confidence: 55%
“…In all previous studies, more than 10 mL pelvic free fluid was rarely reported in asymptomatic individuals. Less than 10 mL fluid has been assumed normal in all age groups without evidence of underlying disease [2, 4, 22]. However in this study, 15% of females and 3% of males had more than 10 mL fluid during puberty transition.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations